2008
DOI: 10.1016/j.bmcl.2008.07.074
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a natural product-inspired eight-membered ring lactam library via ring-closing metathesis

Abstract: We have prepared a novel speculative eight-membered lactam demonstration library based on the skeletal structure of the potent antitumor marine natural product octalactin A. The basic scaffold was readily constructed in a convergent fashion via ring-closing metathesis chemistry from the corresponding diene amides. A cursory examination of the biological properties of the library validates the relevance and significance of these structures. KeywordsEight-membered; Natural product; Lactam; Library; Ring-closing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…The chemical syntheses and structures of most of these novel compounds have already been published or will be reported in detail elsewhere (3,4). This study was initiated after we discovered that spectrophotometric time scans demonstrated the ability of 4–25 μ M concentrations of DL-II-D7 to increasingly mimic the inhibitory activity of 41–256 nM concentrations of pravastatin on the catalytic domain of purified HMG-CoA reductase in a cell-free assay in vitro (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The chemical syntheses and structures of most of these novel compounds have already been published or will be reported in detail elsewhere (3,4). This study was initiated after we discovered that spectrophotometric time scans demonstrated the ability of 4–25 μ M concentrations of DL-II-D7 to increasingly mimic the inhibitory activity of 41–256 nM concentrations of pravastatin on the catalytic domain of purified HMG-CoA reductase in a cell-free assay in vitro (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of the 10-member sublibrary of novel unsaturated eight-membered lactam compounds used in this study (DL-II-D4 and DL-II-D7; GG-II-Ala29, GG-II-G3-cis, and GG-II-G7; NB-IX-Gly27, NB-IX-Gly35, NB-IX-Gly38, NB-IX-Gly44 and NB-IX-Gly46) was performed in the convergent-divergent manner described previously (3,4). In general, ring-closing metathesis (RCM) of a collection of diene amides (prepared from the carboxylic acids and the fluorinated secondary allyl amine), was followed, after deprotection, by parallel derivatization of the resulting cyclic secondary amine scaffold (Scheme 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, no product was detected without the addition of NaOAc and a large amount of the substrate remained (Table 1 After obtaining optimized reaction conditions, we first evaluated the effect of substituents on the aniline moiety (Figure 2). Anilines bearing substituents like fluoride, chloride, or no substituent at the para-position showed good reactivity in the synthesis of nine-membered lactams (2)(3)(4). Notably, the electron-rich amides, which failed previously, 22 were now suitable under the current conditions.…”
Section: Resultsmentioning
confidence: 90%
“…Medium-sized lactams are prevalent structural motifs found in a variety of natural products and medicinal compounds. [1][2][3][4][5][6] Owing to unfavorable enthalpic and entropic barriers during the transition states of forming medium-sized rings, access to these molecules is challenging. Conventionally, direct intramolecular head-totail cyclization strategies suffer from requirements of high-dilution solvents and competing intermolecular reactions.…”
Section: Introductionmentioning
confidence: 99%